Analisis Faktor-faktor yang Mempengaruhi Migrasi Masuk ke Kota Denpasar - Trendyari, A.A. Tara; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
This study aimed to analyze the influence of socio-economic variables such as income, employment, investment, educational services access, and health services access of the in-migration to Denpasar City. The location of this research is in Denpasar City, with number of samples are 100 respondents, obtained by stratified random sampling method based on region distrata districts in Denpasar City. The data were collected using questionnaires and interviews. While the analysis techniques used in this study is binary logistic regression. Based on the results of analysis showed that the variable income, employment, investment, educational services access, and health services access simultaneously significant influence of the in-migration to Denpasar City. Variable income, employment, investment are positive influence and significant, while variable educational services access and health services access no significant influence of in-migration to Denpasar City. Variable income most dominant influence of the in-migration to Denpasar City.
Keywords: migration, income, employment, investment, educational services access, health services access